1982
DOI: 10.1136/jnnp.45.5.396
|View full text |Cite
|
Sign up to set email alerts
|

Congophilic angiopathy of the brain: a clinical and pathological report on two siblings.

Abstract: SUMMARY Clinical and histological accounts are given of a sister and brother, dying aged 61 and 56 years respectively after illnesses lasting 5-6 years marked by a progressive mental and physical disability. The family history suggested transmission by a dominant gene. The histological findings were of a very severe congophilic angiopathy confined to the brain, spinal cord and leptomeninges and giving rise to multiple haemorrhages and softenings. There were, in addition, abundant amyloid-containing "plaques" o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 19 publications
0
23
1
Order By: Relevance
“…This was in contrast with the other cases of severe CAA coexisting with AD where such lesions were found occasionally in a pari o f the vessels with CAA: Similar cases of dementia characterized by severe CAA with perivascular plaque formation have been reported [9,[24][25][26][27][28][29][30][31]. The reported cases were familial [24-26, 29, 30] or nonfamilial [9,27,28,31]; NFT were present [9,[24][25][26][29][30][31] or absent [27,28]. Some have been discussed as atypical AD [26,31], and others as the other entities including 'primary idiopathic cerebrovascular amyloidosis' [28].…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…This was in contrast with the other cases of severe CAA coexisting with AD where such lesions were found occasionally in a pari o f the vessels with CAA: Similar cases of dementia characterized by severe CAA with perivascular plaque formation have been reported [9,[24][25][26][27][28][29][30][31]. The reported cases were familial [24-26, 29, 30] or nonfamilial [9,27,28,31]; NFT were present [9,[24][25][26][29][30][31] or absent [27,28]. Some have been discussed as atypical AD [26,31], and others as the other entities including 'primary idiopathic cerebrovascular amyloidosis' [28].…”
Section: Discussioncontrasting
confidence: 44%
“…The clinical and pathological heterogeneity in those patients [9,[24][25][26][27][28][29][30][31] may reflect the molecular difference of cerebrovascu lar amyloid proteins. In a British familial CAA character ized clinically by dementia, spastic paresis, and ataxia, and pathologically by CAA with nonneuritic plaque for mation [24,25,29,30], the amyloid protein was recently reported not to be [3 protein, but a novel protein [48], Recently, a Japanese demented patient presented with PrP amyloid angiopathy and NFT in association with codon 145 mutation of the PrP gene [9]. In our case, the deposited amyloid protein was inimunohistochemically demonstrated to be P protein; the case was considered to be a variant of AD characterized by the peculiar neuropa thological feature, severe plaque-like angiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In 1933, Worster-Drought first described a British kindred with presenile dementia and spastic paralysis (WorsterDrought et al 1933(WorsterDrought et al , 1944, and subsequently an identical condition was reported in two siblings (Griffiths et al 1982). Both families were later shown to be part of the same pedigree.…”
Section: Familial British and Danish Dementiamentioning
confidence: 96%
“…Familial British dementia, an autosomal dominant neurodegenerative disorder, is characterized by progressive spastic tetraparesis, cerebellar ataxia and dementia 2,3 . The principal pathological hallmarks of FBD include the presence of non-neuritic plaques and amyloid angiopathy in the cerebellum, hippocampus, amygdala and cerebral cortex, hippocampal neurofibrillary tangles and ischemic white matter changes [1][2][3] .…”
Section: Articlesmentioning
confidence: 99%